2019
DOI: 10.3390/ani10010048
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Losses of Fat and Fatty Acids in Growing Pigs Are Not Affected by Vegetable Oil Sources but by the Method of Estimation

Abstract: An experiment was conducted to determine the effect of oil sources with differing degrees of fatty acid saturation on endogenous losses of fat (ELF) and fatty acids (ELFA) in growing pigs, in which endogenous losses were estimated by two methods. Sixty-eight growing barrows (initial body weight 31.13 ± 4.44 kg) were randomly allotted to a completely randomized design with 17 diets. Sixteen added-oil diets were formulated by adding four levels (2%, 4%, 6% and 8%) of palm oil (PO), soybean oil (SBO), flaxseed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The unsaturated oil (canola oil) had a greater digestibility value than that of the saturated oil (palm oil). This observation agrees with results showing a greater digestibility of canola oil versus palm oil in growing pigs [ 5 , 22 , 23 ] and weaned pigs [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The unsaturated oil (canola oil) had a greater digestibility value than that of the saturated oil (palm oil). This observation agrees with results showing a greater digestibility of canola oil versus palm oil in growing pigs [ 5 , 22 , 23 ] and weaned pigs [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The negative values for AID of CF indicate that there were high endogenous losses in Eimeria -infected broilers. Endogenous fat from the gastrointestinal tract includes bile, cell debris, intestinal secretions, and microbial lipids [ 59 ]. Adams et al [ 60 ] demonstrated that infection of E. acervulina decreased the secretion of bile, which has an essential role in fat digestion by emulsifying fat in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this experiment showed that the SID of fat across all oil sources were more than 90%, which indicates that the dietary fat is an extremely digestible energy feed with high absorption efficiency in the digestive tract of animals [ 1 , 32 , 37 ]. Previous research regarded the fat-free diet method as the proper approach to determining the standardized digestibility of fat and fatty acids in plant oils [ 11 , 38 ]. The present experiment was the first one to comprehensively determine the SID of fat and fatty acids from ten oil sources using the fat-free diet method.…”
Section: Discussionmentioning
confidence: 99%